GASTROINTESTINAL SYMPTOMS AND THE BEST THERAPY WITH SEVERITY OF CORONAVIRUS DISEASE 2019: SYSTEMATIC REVIEW - Nudiayona, Agata (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Because the COVID-19 virus has spread around the world so quickly, there is a severe shortage of medical supplies in every region of the planet. This is especially true of the supplies that are necessary for the treatment of patients who are in a critical condition, such as intensive care and ventilators. Emerging diseases such as COVID-19, which manifest in the respiratory system, are a significant reason for worry. In addition, people who have been identified with COVID-19 frequently have diarrhea in addition to other gastrointestinal symptoms; despite this, the relevance of these data has not been established. Remdesivir, lopinavir/ritonavir (LPV/r), steroids, tocilizumab, interferon alpha or beta, ribavirin, hydroxychloroquine/chloroquine alone or in combination with azithromycin, and baricitinib are some examples of drugs that have the potential to be useful in the treatment of HIV/AIDS. Other potential drugs include baricitinib. Because symptoms of the gastrointestinal tract (GI) and malfunction of the liver are frequently observed in COVID-19, it can be difficult to differentiate between the indicators of the illness and the potential negative consequences of treatment. When deciding on the most effective course of therapy for COVID-19 patients, medical professionals need to take into account the possibility that gastrointestinal (GI) symptoms and liver dysfunction are caused either by disease presentations or by drug side effects.